2019
DOI: 10.1371/journal.pone.0210311
|View full text |Cite
|
Sign up to set email alerts
|

HPV prevalence and genotype distribution among women in Shandong Province, China: Analysis of 94,489 HPV genotyping results from Shandong’s largest independent pathology laboratory

Abstract: BackgroundData regarding human papillomavirus (HPV) prevalence and genotype distribution are limited in Shandong Province, China. Therefore, we investigated the recent HPV prevalence and genotype distribution among females in Shandong and aimed to provide comprehensive data to guide HPV-based cervical cancer screening and HPV vaccination for this population of Chinese women.MethodsHPV testing results of 94,489 females were retrospectively reviewed and extracted from the database of Jinan KingMed Diagnostics, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
56
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 54 publications
18
56
5
Order By: Relevance
“…HPV infection rate varies between nations and regions. The overall prevalence of HPV (34.4%) among women in our study was higher than that in other regions of China, such as Shanghai (31.84%) [14], Shandong (28.4%) [2], Zhejiang (22.8%) [15], and Jiangxi (22.49%) [16]. Understanding the epidemiological characteristics of HPV infection is of great importance to the development of prevention and control strategies for HPV.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…HPV infection rate varies between nations and regions. The overall prevalence of HPV (34.4%) among women in our study was higher than that in other regions of China, such as Shanghai (31.84%) [14], Shandong (28.4%) [2], Zhejiang (22.8%) [15], and Jiangxi (22.49%) [16]. Understanding the epidemiological characteristics of HPV infection is of great importance to the development of prevention and control strategies for HPV.…”
Section: Discussionmentioning
confidence: 54%
“…HPV infection exhibits a distinct tropism for mucosal or cutaneous squamous epithelia, and the position where cancer derives depends on the site of HPV invasion. HPV infection is involved in a series of diseases of the vagina, vulva, penis, and anus, as well as anogenital warts and recurrent respiratory papillomatosis [2]. In 2018, there were estimated to be 570,000 new cases of cervical cancer and 311,000 deaths related to cervical cancer, representing 6.6% of all female cancers; cervical cancer was ranked as the fourth most frequently diagnosed cancer and the fourth leading cause of cancer death in women [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The HPV infection prevalence vary considerably from geographically to populations. Globally, the highest HPV infection rate is Sub-Saharan (25.6%), South America (14.3%), Asia (8.7%), Europe (5.2%) of women with normal cytology, [6].Even within a country, the HPV infection rate varies., It is 28.4% in northeast china, 20.16% in south China and 14.2% in northwest China [13][14][15]. The prevalence of neighboring southwest provinces is 26.2% in Chonqing, 16.95% in Guizhou, 12.9% in Yunnan [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous reports, HPV positive rates range from 6.70% to 44.50% in China [11]. Notably, Western Asia (1.70%) and North America (4.70%) had a low rates of HPV infection, while East Africa (33.6%) and the Caribbean (35.4%) had a high rates of HPV infection [17][18][19]. HR-HPV genotype distribution was also heterogeneous, ranging from 9.90%-27.50% in China, which is 15.17% in current study, as with that in Guangdong (20.02%), Guiyang (20.45%) and Nanning (22.28%) [20].…”
Section: Prevalence Of Lr-hpv Only Hr-hpv Only and Mixed Lr-and Hr-mentioning
confidence: 94%
“…Evaluations in the United State showed that young women had the highest HPV prevalence [3], consistent with our the ndings of the highest HPV prevalence (33.11%) among women aged less than 21 years. Young women often have a high infection rate, mainly because they are sexually more active before their immune systems become less sensitive [17]. Although they were known to have high risks for HPV infection, however it is temporary and supposed to disappear within a year or two, and thus its prevalence declined gradually with respect to ages [18].…”
Section: Prevalence Of Lr-hpv Only Hr-hpv Only and Mixed Lr-and Hr-mentioning
confidence: 99%